Studi Pengaruh Motivasi Kerja dan Pengembangan Karir terhadap Organizational Citizenship Behavior (OCB) melalui Kepuasan Kerja - Putro, Ericko Widodo; Sutianingsih, Sutianingsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The primary goal of this study is to investigate the interrelationships among work motivation, career progression, and OCB among Ahass Boyolali employees, utilizing Job satisfaction as a mediating factor. The approach used in this research encompassed a descriptive-causal research design within a quantitative framework. All 35 employees at the Ahass Boyolali site participated in the survey. The study collected data using a 5-point response structure and a likert scale. The research hypotheses were tested using the PLS-SEM method implemented in the SmartPLS software. The following are the hypotheses derived from this research: First, this study does not prove that work motivation directly and significantly impacts OCB. Second, it has been demonstrated that professional advancement significantly impacts OCB. Third, rising job satisfaction is affected considerably by work motivation; Fourth, job satisfaction is not directly affected by professional advancement; Fifth, OCB is significantly affected by job satisfaction; Sixth, job satisfaction acts as an intermediary between work motivation and OCB Seventh, the positive relationship between work motivation and OCB is partially explained by job satisfaction.